The Human Initiative Organization as Initiation Child Protection in Bengkulu - Ishak Fadlurrohim (International Journal of Science and Society, 2023)
This research is descriptive quantitative research. The research aims to understand the role of organisations human initiative in child protection in Bengkulu. This study using data collected primary and interviews. This study using the quantitative analysis, multiple linear regression analysis and analysis determined with the help of the SPSS 25 application. Populations in this study are the stewards and volunteers of the human organization's initialized 30 responders consist of 10 male responders 33.3 % and 20 female responders 66.7 %. The responders are the stewards or volunteers of the human initiative organization are college students from various study programs that have interest in the social services., empowerment and child education problems. The results of the research obtained were tested using test t and test f shows the impact of active roles, Participatory roles and passive roles against good child protection non-discrimination, The best interests of the child, The right to live, Survival and development, An award for the child's opinion. Research shows the average human organization's role in what appears to be an active role 21.97%, participatory role 21.67% and passive role 17.47%. In addition to child protection applied to non-discrimination 13.40 %, child's best interests 13.00 %, right to live 11.50 %, survival and development 12.80% and award to child 17%. An active role having influence stimultan against non-discrimination and a positive influence on the interests of children and the right to life and survival covering basic needs, education and social welfare or temporary habitation. We still do not have significantly affect the award stimultan in the opinion. It is grounded in part in accordance with the rules on the run / norm focus on children through the organization constructed with standardized child safe guarding policy and joint commitment through the HOME (hug, opportunity, mentality, education) and based on the style of leadership that is flexible and responsible in any decision making by approaching co-creation strategy. The role of participatory having influence in stimultan against non-discriminatory, the interests of children and having the right to life and significantly affect the child survival. Meanwhile the role of participatory have no influence on the interests of children and survival and awards toward the opinions of children significantly. It is caused by restriction existing programs as well as the awareness organization / volunteers related convention limited the rights of the child. In addition can look through the dynamic role owned in carrying out rights and obligations and needs conditional made by the organization of the needs in fulfilling formal (human needs, productivity and profitability of the organization and quality of human life) in Human Service Organizations. Passive roles have a significant impact on non-discrimination. However, it has no partial impact on non-discrimination. On the other hand, the passive role has a positive influence on the interests of the child and the rights of the child due to human initiative becomes a symbol/reference of the organization in the protection and enforcement of the rights of the child. In addition, passive roles have an influence on the right to life and survival of the child. Passive roles do not have a significant influence on the appreciation of the opinion of the child. This is because human initiative is defined as a symbol/reference organization on the standard of child service both normatively and comparatively for Pathfinding, Alignment and Empowering.